2019
DOI: 10.3390/cells8070666
|View full text |Cite
|
Sign up to set email alerts
|

NS5A Gene Analysis by Next Generation Sequencing in HCV Nosocomial Transmission Clusters of HCV Genotype 1b Infected Patients

Abstract: Background: The aim of the study was to investigate the intra-host variability through next-generation-sequencing (NGS) of the NS5A-gene in nosocomial transmission-clusters observed in two Italian hospitals among hepatitis C virus (HCV)-genotype-1b infected patients. Methods: HCV-sequencing was performed by Sanger-sequencing (NS3 + NS5A + NS5B) and by NGS (NS5A, MiSeq-Illumina) in 15 HCV-1b infected patients [five acute with onco-hematologic-disease and 10 (4/6 acute/chronic) with β-thalassemia]. Resistance-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…We have also identified A218S in patients never subjected to SOF treatment, despite evidence that this substitution may jeopardize the access of SOF-triphosphate to the catalytic site of NS5B [37]. Bellocchi et al (2019) identified K78R and T64A in NS5A and C213S, S231N, N231S and A218S in HCV G1b-infected patients naïve to DAAs [43]. T64S in NS5A was listed as a secondary substitution accompanying P58S and Y93H in HCV G1b-infected patients who failed DCV therapy, with a resistance level of EC 50 <1 nmol/l [44].…”
Section: Discussionmentioning
confidence: 99%
“…We have also identified A218S in patients never subjected to SOF treatment, despite evidence that this substitution may jeopardize the access of SOF-triphosphate to the catalytic site of NS5B [37]. Bellocchi et al (2019) identified K78R and T64A in NS5A and C213S, S231N, N231S and A218S in HCV G1b-infected patients naïve to DAAs [43]. T64S in NS5A was listed as a secondary substitution accompanying P58S and Y93H in HCV G1b-infected patients who failed DCV therapy, with a resistance level of EC 50 <1 nmol/l [44].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States (US), HCV prevalence in HD units ranges from 5% to 44%, 3 and HD treatment is considered a risk factor for HCV transmission. A 1993‐1995 study in Greece estimated that 10% of patients seroconverted to HCV during their first 5 years of HD 20,22 . HCV genotype clustering suggests that transmission spreads within HD units 20,22 .…”
Section: Epidemiologymentioning
confidence: 99%
“…A 1993‐1995 study in Greece estimated that 10% of patients seroconverted to HCV during their first 5 years of HD 20,22 . HCV genotype clustering suggests that transmission spreads within HD units 20,22 . Hepatitis D and G infections are also more common among dialysis patients than in the general population.…”
Section: Epidemiologymentioning
confidence: 99%
“…[ 6 , 7 ] At present, there are 3 typical sequencing technologies in NGS field, including 454 from Roche Company (Switzerland), Solexa from Illumina Company (USA), and SOLID from ABI Company (USA), and sequencing technologies such as IonTorrent, Heliscope, Nanopore, SMRT, IonPGM and GeXp. [ 8 ] Among them, the 454-sequencing technology can read about 700 bp in length, and the sequencing time is 18 to 24 hours. The method adopted is pyrosequencing with an accuracy of 99.9%.…”
Section: Introductionmentioning
confidence: 99%